Does institutional quality matter in the financial development-economic complexity nexus? Empirical insights from Africa - Clement Olalekan Olaniyi; Nicholas M. Odhiambo (Research in Globalization, 2023)
Purpose This study examines the moderating role of institutional quality and its threshold in the African financial development-economic complexity nexus. This objective follows the argument that institutional quality influences the financial system's efficiency in allocating resources to innovative initiatives and activities that increase productivity knowledge and technical capabilities in an economy's production system to produce complex products and exports. Design/methodology/approach To achieve these objectives, this study adopts novel and robust approaches such as the system generalized method of moments (GMM), the Driscoll-Kraay nonparametric covariance matrix estimator (DK), the method of moments quantile regression, and a dynamic panel threshold to analyze the annual dataset of 29 African countries covering 1995-2020. Findings This study establishes robust and persistent evidence of interdependence, intertwining, and heterogeneity among African countries. Both mean-based (GMM and DK) and quantile regressions consistently demonstrate that financial development and institutional quality separately enhance Africa's economic complexity across quantiles. In contrast, institutional quality drains financial development's contribution to economic complexity when the coefficients are significant. The moment-quantile regression reveals that institutional quality complements financial development to support economic complexity from the 10th to 30th quantiles, but the coefficients are insignificant. The threshold estimation confirms nonlinearity and the institutional quality threshold estimate is 5.73 on the ordinal scale of 10. On average, only six African countries exceed the threshold, while others operate below the benchmark. Research limitations/implications Based on the findings, African financial systems operate within weak institutional frameworks. These phenomena allow rent-seeking, opportunism, corruption, and sharp practices, which divert financial resources from innovative activities and investments in research and development, human capital development, technology, high-tech infrastructure, and entrepreneurial innovation. As a result, Africa's institutional quality impairs the financial sector's ability to spur economic complexity upgrades. African economies need better institutional architectures to maximize financial development's benefits of upgrading economic complexity. The policy implications and recommendations of this study are more relevant to African settings and situations. Thus, other scholars are encouraged to conduct similar research for other continents to enrich the study's outcomes. Originality/value The following are the highlights of this study's novelties: 1.) To the best of the authors' knowledge, this is the first study to examine the moderating role of institutional quality in the financial development-economic complexity nexus in Africa using estimators that account for cross-sectional dependence, distributional effects, and heterogeneous effects (the Driscoll-Kraay nonparametric covariance matrix estimator (DK) and the method of moment quantile regression). 2.) Unlike earlier research, this study establishes a threshold of institutional quality in the financial development-economic complexity nexus. We propose that the institutional structures that govern Africa's financial systems be examined and trimmed. This move helps to phase out the inherent inadequaciesthat drain financial development's contributions to economic complexity.
Keywords: 330; Economic complexity; Financial development; Institutional quality; Productivity knowledge; Threshold